Carboxymethyl β-cyclodextrin grafted carboxymethyl chitosan hydrogel-based microparticles for oral insulin delivery. (15th October 2020) - Yang, Yu; Liu, Yang; Chen, Shengqin; Cheong, Kit-Leong; Teng, Bo
Highlights: CMC-g-CMCD hydrogel microparticles were prepared for oral insulin delivery. 90 % of the insulin was retained inside the hydrogel in the gastric environment. Hydrogel microparticles were mainly via paracellular pathway across Caco-2 cell. Oral insulin by hydrogel exhibited a long-acting and stable hypoglycemic effect. Abstract: This study was aimed at utilizing polysaccharides for the development of effective hydrogel microparticles for oral insulin delivery that has a controlled, and sustained release to enhance paracellular transcellular absorption. Carboxymethyl β-cyclodextrin grafted carboxymethyl chitosan hydrogels (CMCD-g-CMCs) were prepared from carboxymethyl β-cyclodextrin (CMCD) and carboxymethyl chitosan (CMC) using a water-soluble carbodiimide as a crosslinker in the presence of N-hydroxysuccinimide. After synthesis, the hydrogel structures were determined via FT-IR and XRD analyses. The porous structure of hydrogels was confirmed by SEM observations and swelling behaviours. The insulin release behaviours were found to betriggered by pH in vitro . Results showed that insulin was successfully retained inside the hydrogels in the gastric environment and slowly released following passage to intestinal conditions. The stability of the secondary structure of insulin was studied by dichroism circular (CD) and fluorescence (FL) spectrophotometer measurement. There was no significant difference in the secondary structure between the native and released insulin. In vitro studies revealed that the hydrogel microparticles exhibited non-cytotoxicity and were transported across the Caco-2 cell monolayers mainly via the paracellular pathway. In order to examine the effectiveness of hydrogel-based sustained release microparticles in delivering insulin in vivo, we administered different insulin-loaded hydrogel microparticles to diabetic mice. In these studies, we found that the insulin-loaded hydrogel microparticles provided a significant and sustained (ranging from 6 h to 12 h) reduction in the blood glucose levels of diabetic mice compared with subcutaneous injection. Overall, these findings demonstrate that CMCD-g-CMCs may be a promising protein carrier for use in oral drug delivery.